TRANSVERSAL TECHNOLOGY AS A KEY IDEA FOR FUTURE GLOBAL ECONOMIC GROWTH - Loso Judijanto; M. Fakhriansyah; K. M. Faisal Reza (Adisam Publisher, 2025)
Transversal technologies play a vital role as a key driver in future global economic growth. In this context, technology not only functions as a tool, but also as a driving force that significantly changes the economic and business paradigm. Innovation in this sector, driven by technology, can improve people's welfare and strengthen the cultural identity of the nation. Transversal technologies are important forces behind innovation and development, and in the years to come, their significance is only predicted to increase. These technologies will probably have a significant impact on how many industries and society as a whole develop in the future as they continue to progress. Transversal technologies have the ability to address some of the major issues facing humanity in addition to spurring innovation and economic progress. Transversal technologies not only serve to improve efficiency and productivity, but also act as key drivers in creating new opportunities and driving inclusive and sustainable economic growth. Collaboration between stakeholders, including governments and the private sector, is essential to harness this potential and address future challenges.